(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
A body worn camera is a device that is clipped to a police officer’s chest that records audio and video footage that can be reviewed and used as evidence. This device is usually operated by police patrol officers when conducting their duties. This research is all about determining the underlying factors regarding the perception of the community and police patrol officers in the mandatory use of body-worn cameras. Based on the study, the police patrol officers and the community stated that the use of body- worn cameras during police operations eliminates uncertainty and increases transparency. Likewise, as long as the policies and guidelines are strictly adhered to, footage captured with a body-worn camera serves as reliable evidence in court. Body-worn cameras, on the other hand, are difficult to conceal and easy to discharge during police operations. Similarly, police officers still rely on an alternative recording device during police operations, and there is still a lack of body-worn cameras in all police stations. This study focuses on determining the perception of the community and police patrol officers of the mandatory use of body-worn cameras.